IMPLEMENTASI PROGRAM PERCEPATAN PEMBANGUNAN INFRASTRUKTUR DESA DAN KELURAHAN (PPIDK) KASUS DESA KUALA PANDUK KABUPATEN PELALAWAN TAHUN 2013-2014 - Huda, Tengku Rajib; Anwar, Khairul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The problem in this study is whether the Group of Governmental Kuala Panduk Village as a contractor at the village level and BPMPD Pelalawan as policy makers, understand and can implement this program in accordance with the instructions and the extent of public support in the review of social, cultural, political and economic factors a factor that into effect in practice. Theoretical concept that is in use is policy and policy implementation.This research uses descriptive method. In collecting the data, researchers use interviewing techniques, observation and documentation. These results indicate that the Infrastructure Development Acceleration Program Implementation Village and Village (PPIDK) Case Kuala Panduk Village, Pelalawan Regency Year 2013 to 2014 have not been up to equitable development, increase revenue and employment for the people of the village of Kuala Panduk due to budget constraints.Keywords: Policy, PPIDK program, Policy Implementation